Helping friends in need or helping oneself? The case of China’s international disaster management policy in the 2010s - Lauri Paltemaa (Osaka University of Economics and Law - Asian Research Institute, 2022)
Abstract
This article analyzes how the People’s Republic of China engages in international disaster management (IDM). The paper sets out to answer especially the question of how these activities benefit its own disaster management capabilities. In order to answer the question, the study analyzed public archival materials of news reports concerning China’s bilateral and multilateral IDM activities between May 2013 and May 2018, retrieved from the China National Commission for Disaster Reduction’s online database. This data was analyzed quantitatively and qualitatively. The article argues that Chinese IDM engagements are active and have a global reach, but are at the same time selective in their nature. The PRC uses IDM to position itself as a “leading developing country” through its active IDM engagements with other developing countries, while at the same time also seeking to benefit from developed countries’ disaster management know-how and accepting humanitarian aid only in case of large natural disasters.